Philosophical troubles collected papers. Volume 1 - Kripke, Saul A., 1940- (New York ; Oxford : Oxford University Press, 2011)
This text is the first of a series of volumes collecting the essential articles by the eminent and highly influential philosopher Saul A. Kripke. It presents a mixture of published and unpublished articles from various stages of Kripke's storied career.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Philosophy